Na okraj české reformace - Pavera, Libor (Slavia Centralis, 2020)
The author of the text addresses the Czech Reformation, he reflects on the beginnings of the reform movement in the Czech environment (referring to the change of mindset concerning changes in education, art, culture, etc.). From a bird’s eye view, the author looks at Czech history in its shift to modernity and reveals the significant trail the Czech type of Reformation left behind in the history of Czech lands. He is following Czech Reformation since the time of the Roman emperor, Karel IV (Charles IV) with his efforts for a different Church to the 20th Century, when the problem of Reformation manifested itself in a rather philosophical dispute – concerning the two-armed religious trend in the history of Czech citizens. T. G. Masaryk and J. Pekař participated in the dispute as well as their students and followers of two different ideas. It is the so-called dispute about the meaning of Czech history, which has not been resolved until today and there may be one of the answers to the question about the type of relationship of a Czech citizen to faith, the church (devotion) and the domineering religious feeling in general. The author concludes that in Europe as well as in the Czech Republic the Reformation was never a single stream.